(untitled) (Medicine Today, 2025)
Introduction: Coronary artery disease (CAD) becomes a major cause of death. CAD is an atherosclerosis process, which progressively develops into plaque that will lead to stenosis of coronary artery lumen. Several studies found that Thrombolysis in Myocardial Infarction (TIMI) risk score is an significant marker of the severity of coronary artery disease. Objectives: To see the correlation between TIMI risk score and Gensini score in patient with Non-ST segment elevation myocardial infarction. Materials and Methods: This cross-sectional observational study was conducted in the Department of Cardiology, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from 1st September 2018 to 31st August 2020. Total 73 patients with NSTEMI who underwent coronary angiography (CAG) were selected. Patients were divided in two groups: Group A = TIMI score ≤4 and Group B = TIMI score >4. Coronary angiography was performed by experienced interventional cardiologist to assess severity of CAD. Angiographic severity was assessed by Gensini score. Results: This study was conducted on total 73 patients. Age of the patients ranged from 21 to 70 years with the mean age of 51.08 ± 11.11 years. Among them 55 (75.3%) patients were male and 18 (24.7%) patients were female. Total 45(61.6%) patients were in group-A and 28 (38.4%) patients were in group-B. Mean TIMI risk score was 2.89 ± 1.05 in group-A and 5.71 ± 0.76 in group-B. Majorities of the patients in high TIMI risk score group had hypertension, diabetes, dyslipidaemia and history of smoking but most of them had no family history of CAD. Mean Gensini score was 20.47± 18.27 in group-A and 35.00 ± 25.04 in group-B, the difference was significant (p=0.006). There was a positive linear correlation between TIMI risk score and Gensini score (r=0.497; p= <0.001). Conclusion: This study demonsrated that TIMI risk score has positive correlation with Gensini Score in angiographic study in patients with NSTEMI. Medicine Today 2025, Vol.37 (2): 174-178